Boosting photocatalytic H2 evolution through interfacial manipulation on a lotus seedpod shaped Cu2O/g-C3N4 p-n heterojunction. Issue 3 (11th January 2023) - Tian, Fengyu; Wu, Xinyao; Liu, Shuai; Gu, Yawei; Lin, Zezhou; Zhang, Honglei; Yan, Xuemin; Liao, Guangfu
Abstract : A novel lotus seedpod shaped Cu2 O/g-C3 N4 p–n heterojunction composite was fabricated by in situ filling the g-C3 N4 framework with Cu2 O hollow nanospheres for efficient photocatalytic hydrogen evolution. Abstract : Precisely modulating the interfacial contact of heterojunction photocatalysts and regulating the spatial transfer of photoexcited charge carriers play a significant role in promoting the photocatalytic efficiency. Herein, a novel lotus seedpod shaped Cu2 O/g-C3 N4 p-n heterojunction composite was fabricated by in situ filling the g-C3 N4 framework with Cu2 O hollow nanospheres. The obtained Cu2 O/g-C3 N4 p-n heterojunction presents superior photocatalytic H2 evolution activity with an optimal production rate of 637.5 μmol g −1 h −1, which is 40 times higher than that of pure g-C3 N4 . Through the combination of characterization and density functional theory (DFT) calculations, the boosted photocatalytic activity of Cu2 O/g-C3 N4 is attributed to the optimized p-n heterojunction structure with a proper band configuration and suitable heterojunction interface, which can improve the spatial separation of the photoexcited charge carriers and promote the charge transfer efficiency. This investigation is expected to highlight the promising scope of rationally constructing a p-n heterojunction with ideal interfacial contact, and intelligent regulation of the spatial separation of photoexcited charge carriers for photocatalytic water splitting.